Oral Cancer Screening Among Indian Women within Reproductive Age-Group: Coverage, Determinants, Socio-Economic Disparities - Dr. Pritam Halder; Dr. Subham Kansal; Dr. Sushanta Sarkar; Dr. Anamika Das (Journal of Medical Care Research and Review, 2024)
Objective: This study was conducted to assess the coverage, determinants, and socio-economic disparities in oral cancer screening among Indian women within reproductive age group. Materials and Methods: A sample of 724,115 women aged 30-49 years from National Family Health Survey-5 (2019-21) were analysed. Self-reported ever screening for oral cancer was used as outcome variable. A set of socio-economic and risk factors associated with oral cancer screening were used as predictors. Logistic regression was used to assess the factors associated with cancer screening, concentration index and concentration curve were used to assess the socio-economic inequalities in oral cancer screening uptake. Results: A total of 348,882 participants were included in final analysis after all exclusions. Uptake of oral cancer screening was increasing with increase in wealth Index [Middle wealth index, adjusted odds ratio, AOR 1.35 (1.07-1.70), Richer AOR 1.43 (1.12-1.84), Richest AOR 1.60 (1.20-2.13)], higher educational status and in obese women [AOR 1.28 (1.02-1.63)]. While the women belonged to Muslim religion [AOR 0.68 (0.56-0.84)] and schedule tribes [AOR 0.70 (0.53-0.84)] had lower odds for screening uptake. Women from South Indian states [AOR 9.58 (7.60-12.07)], West Indian states [AOR 3.81 (2.88-5.04)], Central India [2.48 (1.95-3.14)] and North-east Indian states [1.65 (1.20-2.27)] had higher odds of oral cancer screening uptake compared to North Indian states. Conclusion: Screening uptake varies among the socio-economic status and different regions of country. Despite the operational guidelines and provision for screening at public health centres, the screening uptake is low in the country.